Elevated WNT signaling and compromised Hedgehog signaling due to Evc2 loss of function contribute to the abnormal molar patterning - Zhang, Honghao; Chinoy, Afriti; Mousavi, Paymon; Beeler, Aubrey; Louie, Ke’ale; Collier, Crystal; Mishina, Yuji (Frontiers in Dental Medicine, 2022)
Ellis-van Creveld (EVC) syndrome is an autosomal recessive chondrodysplasia. The affected individuals bear a series of skeleton defects, congenital heart septum anomalies, midfacial defects, and dental defects. Previous studies using Evc or Evc2 mutant mice have characterized the pathological mechanism leading to various types of congenital defects. Some patients with EVC have supernumerary tooth; however, it is not known yet if there are supernumerary tooth formed in Evc or Evc2 mutant mice, and if yes, what is the pathological mechanism associated. In the present study, we used Evc2 mutant mice and analyze the pattern of molars in Evc2 mutant mice at various stages. Our studies demonstrate that Evc2 loss of function within the dental mesenchymal cells leads to abnormal molar patterning, and that the most anterior molar in the Evc2 mutant mandible represents a supernumerary tooth. Finally, we provide evidence supporting the idea that both compromised Hedgehog signaling and elevated WNT signaling between E14.5 and E15.5 due to Evc2 loss of function contributes to the supernumerary tooth formation.